Unveiling belowground allelopathy: 1H-NMR spectroscopy reveals metabolic crosstalk and novel sterols in Cyperus rotundus and Sorghum bicolor co-cultures - Giorgi, Giulia; Patriarca, Adriano; Mura, Francesco; Cocco, Emma; Taggiasco, Serena; Talone, Alessio; Sciubba, Fabio; Miccheli, Alfredo; Tomassini, Alberta; Aureli, Walter; De Vita, Daniela; Zannini, Emanuele; et al. (Frontiers in Plant Science, 2026)
Root exudates are crucial for driving belowground ecosystem dynamics and subterranean chemical interactions. Cyperus rotundus (purple nutsedge) is a highly invasive weed, notoriously resistant to conventional control and causing significant crop losses globally. Sorghum bicolor is well-known for producing allelopathic compounds via root exudates. The metabolic shifts occurring during the direct interaction between C. rotundus and allelopathic crop S. bicolor are yet unexplored. In this study, we established an in vitro protocol for the isolation of root exudates from solid growth medium and employed a non-targeted 1H-NMR spectroscopy approach to fingerprint the hydrophilic and lipophilic root exudates within an in vitro co-culture system. A total of 21 metabolites, including carbohydrates, phenolics, peptides and fatty acids were identified. Notably, three new sterols including (3β)-3-hydroxy-6-methylstigmast-20(22)-en-14-oic acid, 6-methylstigmast-20(22)-en-14-oic acid derivative 1 and 6-methylstigmast-20(22)-en-14-oic acid derivative 2 were univocally assigned. Comparative analysis revealed that co-cultivation induced specific metabolic changes rather than a general increase in exudation. Specifically, the cyanogenic glycoside dhurrin, a primary allelochemical in S. bicolor, significantly decreased in co-cultures, while phytoalexins B, detected in individual C. rotundus exudates, was absent in co-cultures. However, no significant reduction in root biomass was observed for either species over the 12-day experimental period. These findings suggest that while root-root proximity triggers specific secondary metabolites shifts, these changes did not translate into immediate growth inhibition under the tested conditions. This study provides the first non-targeted metabolic profiling of the direct belowground interaction between S. bicolor and C. rotundus and highlights the complexity of modulating allelopathic responses in sterile environments.